Safety evaluation of Weissella confusa SY628 and the effect of its fermentation on the taste and quality of soy yogurt - Liu, Muwen; Li, Xiao; Ye, Tao; Zhao, Liangzhong; Zhang, Xuejiao (Frontiers in Microbiology, 2025)
In the global context, the demand for sustainable protein sources is rising, spotlighting plant—based foods, especially legume products. Fermentation is crucial in developing these foods, as it reduces anti—nutritional factors and improves flavor. But the available fermentation strains for plant—based foods are limited. This study aims to address this knowledge gap by evaluating the safety of Weissella confusa SY628 as a fermentation strain and its impact on the quality characteristics of soy yogurt. The safety evaluation of W. confusa SY628 demonstrated that it possessed no hemolytic activity and was sensitive to a variety of antibiotics, no biogenic amines were produced, suggesting an extremely low pathogenic risk. Furthermore, W. confusa SY628 demonstrated enhanced acid and bile tolerance, characteristics that are indicative of its probiotic properties. The fermentation of soy yogurt was conducted using three distinct organisms: W. confusa SY628, commercial bacterial powder CHS, and a combined starter SYCHS composed of the two aforementioned organisms. The physical, and chemical properties and taste quality of the samples were measured. The results demonstrated that in the SYCHS group, after a 21-day storage period, the pH level was 4.49, the total acidity reached 76.77 °T, and the viable count was 5.81 × 107 CFU/mL, indicating good storage stability. The cohesiveness, viscosity, elasticity, and storage modulus of the SYCHS group were found to be significantly higher than those of the other groups, and the internal network structure was found to be stable. In the SYCHS group, the total amino acid content was determined to be 308.57 μg/g, with umami-tasting amino acids accounting for 22.95%. The total fatty acid content was found to be 1818.95 μg/g, with a notably high polyunsaturated fatty acid content, indicating significant nutritional value. The SYCHS group exhibited the highest number of key flavor components. Substances such as 2,3-butanedione exhibited high ROAV values, contributing to a rich flavor profile. In conclusion, the co-fermentation of W. confusa and commercial bacteria significantly improved the overall quality of soy yogurt, providing a theoretical and practical basis for the innovative development of plant-based foods.